Предмет: Алгебра,
автор: anastasiatyush
Решите уравнение:
x(x-2)(x+1)=x^2(x-1)
???
Ответы
Автор ответа:
0
x(x-2)(x+1)=x²(x-1)
(х²-2х)(х+1)=х³-х²
х³+х²-2х²-2х=х³-х²
х²-2х²-2х=-х²
-х²-2х=-х²
-2х=0
х=0
Ответ: 0.
(х²-2х)(х+1)=х³-х²
х³+х²-2х²-2х=х³-х²
х²-2х²-2х=-х²
-х²-2х=-х²
-2х=0
х=0
Ответ: 0.
Похожие вопросы
Предмет: Геометрия,
автор: youprostakupprost
Предмет: Английский язык,
автор: polina27109111
Предмет: Физика,
автор: orifjonalisherov
Предмет: Геометрия,
автор: mor100
Предмет: Математика,
автор: дарья252